Extension in three spheres: Museum of zoology, education and community - Barros Faria, Michel; Lopes Leodoro, Isteliene (Guará Journal, 2019)
Museums are tools importance in educational formation, they are like portals to a philosophical world that becomes a precious source of knowledge and discoveries. The objective of the study was to expand and strengthen scientific-cultural activities through the dissemination of the Museum of Zoology Newton Baião de Azevedo the UEMG Carangola (MZNB). For this to the extent it was given through itinerant exhibitions, scientific events and lectures in schools of different levels of education. According to the results, the information was disseminated in all the target levels, with a marked arousal of interest. The public in question went beyond the contents present in the formal study, which consequently expanded to the population of Carangola and region. It is necessary to critically review the use of museums in Brazilian education, in order to include and incorporate a relationship between teachers, museums and students